SCOPE OF JOURNAL OF NEONATAL SURGERY - Bilal Mirza (EL-Med-Pub, 2012)
The primary scope of the journal is provision of a platform for publication of evidence-based neonatal surgery. It is the only available journal dedicated to the specialty. Neonatal surgery is often performed by pediatric surgeons in many parts of the world. Surgical neonates, the targeted proportion of the population, are entirely different with other age groups. Their body composition, requirements, immunity, pathophysiology, and response to various diseases are specific to this age group.